SPATIAL AND TEMPORAL PATTERNS OF FISHING USING PAYANG NETS IN STARING BAY, SOUTH KONAWE DISTRICT - Safitri, Dita; Tadjuddah, Muslim; Mustafa, Ahmad; Alimina, Naslina; Arami, Hasnia (Jurusan Perikanan dan Kelautan, 2024)
Staring Bay is a semi-open bay that has a relatively large potential for fishery resources, so it is widely used by fishermen in South Konawe Regency to carry out capture fisheries activities. One of the fishing gear operated by fishermen is payang fishing gear. This fishing gear is operated to catch small pelagic fish. The purpose of this study was to determine the spatial and temporal patterns of fishing with Payang fishing gear in the waters of Staring Bay, South Konawe Regency. The research was conducted from December to January 2022 in the waters of Staring Bay, South Konawe Regency. The analytical method consists of catch composition analysis, CPUE analysis, correlation and determination analysis. Based on the research results, it was found that the fish catch was directly proportional to the distance from the fishing area. The distance of the fishing area that is far from land is 5.50 miles with a catch of 450.00 kg/trip, while the distance of the fishing area that is close to land is 3.35 miles with a catch of 82.50 kg/trip. Apart from that, fishing time also influences catch results, where the highest catch occurs in January reaching 211.91 kg/trip and the lowest catch occurs in December reaching 12.66 kg/trip.Keywords: Payang catch, spatial and temporal patterns, Staring Bay